2005
DOI: 10.1080/13642530500183887
|View full text |Cite
|
Sign up to set email alerts
|

Countertransference issues in psychotherapy with lesbian and gay clients

Abstract: This article briefly reviews literature on responses towards same-sex (lesbian and gay) sexualities from psychoanalytic and 'lesbian and gay affirmative' psychotherapeutic perspectives. An analysis is presented of reports of countertransferential reactions to lesbian and gay clients, obtained from interviews with 14 psychotherapists who work in a lesbian and gay affirmative manner and 18 clients who had received affirmative psychotherapy. Data were subjected to grounded analysis. Participants consistently atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Writers have highlighted the unique dilemmas faced by LGBT therapists in both therapy and supervision (Russell, 2006;Russell & Greenhouse, 1997;Satterly & Dyson, 2008). Grove (2009) has recorded the sense of challenge faced by student counsellors on learning about heterosexist oppression, and their acknowledgement that having LGBT friends and colleagues was an invaluable source of learning (see also Grove, 2003;Guth et al, 2005;Milton et al, 2005;Mohr, 2002). She has also observed that students' gayaffirmative skills and knowledge can remain relatively undeveloped during basic training, even when their expressed attitudes are highly affirmative (see also Mohr, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Writers have highlighted the unique dilemmas faced by LGBT therapists in both therapy and supervision (Russell, 2006;Russell & Greenhouse, 1997;Satterly & Dyson, 2008). Grove (2009) has recorded the sense of challenge faced by student counsellors on learning about heterosexist oppression, and their acknowledgement that having LGBT friends and colleagues was an invaluable source of learning (see also Grove, 2003;Guth et al, 2005;Milton et al, 2005;Mohr, 2002). She has also observed that students' gayaffirmative skills and knowledge can remain relatively undeveloped during basic training, even when their expressed attitudes are highly affirmative (see also Mohr, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, particularly in the early years of their clinical practice, many counsellors' ability to work with LGBT clients is likely to fall short of this ideal. They may lack sufficient life experience to: appreciate that the difficulties faced by LGBT clients; the coping strategies they use; reflect their experiences of living in a largely homophobic world (Dickey, 1997;Grove, 2003); acknowledge the damage that can be caused by making inadvertent heteronormative assumptions (DeBord, 2007;Walker & Prince, 2010); and be wary of the danger that they could collude with, and reinforce, established heterosexual values (Guth, Lopez, Rojas, Clements, & Tyler, 2005;Milton, Coyle, & Legg, 2005;Mohr, 2002;Mohr, Israel, & Sedlacek, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These models can often feel inappropriate and pathologising, as outlined in the main body of this paper, since same-sex couples often work with more flexible family models than their heterosexual counterparts. These findings are endorsed by research conducted in Britain (Annesley & Coyle, 1998;Milton, 1998) where, for example, one therapist, through her line of questioning, suggested that lesbianism was caused by the adverse reaction or violent sexual responses of men towards women, and other therapists struggled to accept the individuals sexual choice by questioning lesbians 'dislike of men' and gay men's 'dislike of women'. This, of course, immediately raises the question of when issues presented in therapy relate specifically to sexual orientation and when they do not.…”
Section: Practice Considerationsmentioning
confidence: 58%
“…Over the last decades, affirmative psychotherapy approaches for LGBT patients have been developed; however, they do not constitute a psychotherapeutic model in itself but instead advocate for the inclusion of specific attitudes into psychological intervention connected with acceptance and understanding of the nature and challenges posed by sexual and gender diversity ( Milton et al, 2002 ; Dillon et al, 2004 ; Kilgore et al, 2005 ; Bieschke et al, 2007 ; Martínez et al, 2018a ). Authors have described a number of affirmative interventions aimed at actively depathologizing sexual diversity and cementing its place as a positive dimension of identity ( Rock et al, 2010 ).…”
Section: Applying the Generic Model For Researching Psychotherapy Witmentioning
confidence: 99%